Microwave activated crushing and grinding of turkish coals and shale for cleaning and desulfurization - Tosun, Yıldırım İsmail (Mining Institute Belgrade, 2015)
The representative samples below 50mm are taken from the local coal area in Şırnak Province and other origin regions. As the coal samples and side rocks, Soma lignite, Tunçbilek lignite, Kütahya Gediz lignite, Şırnak asphaltite, Şırnak coal marl and coal shale were investigated. Heating with microwave of samples of 50 gr at time of 30-480 sec with 900W power in the Bosch laboratory type of Microwave Oven was carried out following roll crushing to minus 4mm and standard Bond Mill grinding. Microwave activated crushing and milling process was efficiently performed. Higher yields occurred about 52 % at 10-5 mm size fraction, 34% at grain size fraction of 3-1.5 mm, 12% at grain size of 0.5mm as grinding breakage. Microwave activated milling was also provided effective grinding with an increase in the Hardgrove Index about 43% for Şırnak asphaltite. Microwave activated milling also provided effective cleaning with a reduction of total sulfur content at 56% in the flotation and about 33% ash reduction in clean coal. As a result, the optimum microwave heat treatment process for coal cleaning plants was defined by making effective use in crushing, grinding and flotation, and the results are discussed.
Keywords: Microwave activation; Crushing; Grinding; Coal cleaning; Desulfurization; Asphaltite